A methodology for virtual assessment of product ergonomics. (2016) - Colombo, Giorgio; Regazzoni, Daniele; Rizzi, Caterina
This paper presents a method, which integrates digital human models (DHM) and virtual prototyping techniques to analyse ergonomic issues of devices to be used by workers. It is based on the comparison between the analysis of AS-IS and TO-BE scenarios with the aim of assessing design concepts, highlighting improvements or worsening and residual deficiencies to be faced. In particular, this paper refers to the case study of display units for groceries or supermarkets. Actually, workers who are in charge of filling the shelves perform highly repeated tasks, potentially dangerous for their health. The AS-IS and TO-BE analysis compares the actual practices with a new scenario in which workers are provided with lifting platforms to load the shelves. The method allows assessing several ergonomics parameters; in this study posture and fatigue are the most relevant. The results achieved with the simulations permitted to propose alternative solutions. Future works in this field concern the standardisation of domain dependant actions virtual human are asked to perform.